2004
DOI: 10.1016/j.jhsb.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Proximal Interphalangeal Joint Release in Dupuytren’s Disease of the Little Finger

Abstract: We present a prospective study, with 3-year follow-up, of the role and outcome of fasciectomy plus sequential surgical release of structures of the proximal interphalangeal joint in Dupuytren's contracture of the little finger. Our treatment programme involves fasciectomy for all patients followed by sequential release of the accessory collateral ligament and volar plate as necessary. Of the 19 fingers in the study, eight achieved a full correction by fasciectomy alone, and in these cases there was a fixed fle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…We did a sequential release of structures (Andrew, 1991) of the PIPJ if the contracture remained greater than 30 after fasciectomy. Sequential PIPJ release has been shown to give good results with few complications (Ritchie et al, 2004). Abe et al (2004) demonstrated that those with a worse preoperative deformity were more likely to have a worse postoperative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…We did a sequential release of structures (Andrew, 1991) of the PIPJ if the contracture remained greater than 30 after fasciectomy. Sequential PIPJ release has been shown to give good results with few complications (Ritchie et al, 2004). Abe et al (2004) demonstrated that those with a worse preoperative deformity were more likely to have a worse postoperative outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Larger, multi-centre series would be beneficial to ensure that the lack of significance demonstrated was not due to type II error. In addition, longer follow-up may show increased recurrence however previous studies have shown that loss of correction occurs predominately in the first three months, 6 which is within the timescale of our analysis.…”
Section: Discussionmentioning
confidence: 49%
“…5 Complete correction is often difficult and recurrence rates are high. [5][6][7][8][9][10] Capsuloligamentous release has been proposed to improved outcomes in some series 5,6,8 but others, even by the same group, have been unable to demonstrate a significant advantage. 9 Van Giffen compared the results of limited fasciectomy, segmental fasciectomy and dermofasciectomy and was unable to demonstrate superiority of any technique as all had equally high rates of recurrent and residual deformity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The PIP can be released but that may lead to pain, recurrence, slower rehabilitation and, on occasions, hyperextension laxity. Although there is no consensus, many surgeons will accept the correction achieved by removal of the Dupuytren's cord without need for further surgical attention to the PIP joint, whereas others will release the joint [100].…”
Section: Recurrencementioning
confidence: 99%